Construction on the Degenerate Poly-Frobenius-Euler Polynomials of Complex Variable. (21st August 2021) - Muhiuddin, Ghulam; Khan, Waseem Ahmad; Al-Kadi, Deena
Abstract : In this paper, we introduce degenerate poly-Frobenius-Euler polynomials and derive some identities of these polynomials. We give some relationships between degenerate poly-Frobenius-Euler polynomials and degenerate Whitney numbers and Stirling numbers of the first kind. Moreover, we define degenerate poly-Frobenius-Euler polynomials of complex variables and then we derive several properties and relations.